2013
DOI: 10.1016/j.infrared.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal quantum dots for mid-IR applications

Abstract: The use of colloidal material offers an interesting alternative to top down approaches for the realization of low cost infrared detectors. We demonstrate photoconduction in thin films of a colloidal material in the mid infrared (up to 7µm), using HgTe colloidal quantum dots. Thin films of the colloidal quantum dots have a large absorption coefficient (>10 4 cm-1), and the photoconductive response is dramatically improved by encapsulating the nanoparticle into an inorganic matrix of As2S3. Such devices show fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…2a, is very close to the calculated value using the Brus equation ( E np =3.50 eV). Photoluminescence (PL) and photoluminescence excitation (PLE) [21] studies were performed to investigate the optical properties of the In 2 S 3 QDs. It can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a, is very close to the calculated value using the Brus equation ( E np =3.50 eV). Photoluminescence (PL) and photoluminescence excitation (PLE) [21] studies were performed to investigate the optical properties of the In 2 S 3 QDs. It can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, CQDs have been widely used in a variety of applications, including solar cells [24], spectrometers [25], phototransistors [26], FPA imagers [27], lasers [28], LEDs [29]. Among all the CQDs systems, mercury telluride (HgTe) CQDs have demonstrated the highest infrared spectral absorption tunability covering main important atmospheric windows including short-wave infrared (SWIR, 1.5-2.5 µm) [30][31][32][33], mid-wave infrared (MWIR, 3-5 µm) [34][35][36][37][38][39][40][41][42], long-wave infrared (LWIR, 8-12 µm) [43,44] and even the terahertz (THz) [45,46], appearing as promising candidates to substitute conventional semiconductors to achieve good detection performance with low cost. This review will be described from the following aspects, including: synthesis of infrared CQDs, infrared CQDs photodetectors, multispectral CQDs photodetectors and CQDs FPA.…”
Section: Synthesis Of Infrared Cqdsmentioning
confidence: 99%
“…Lhullier et al [2426] took the newly improved synthesis and further studied the charge carrier transport properties and optical properties after employing a ligand exchange procedure with ethanedithiol (EDT). Around the same time, Kovalenko et al demonstrated that As 2 S 3 can be used as an infrared transparent ligand for PbS and CdS particles [27] which led to new ligand exchange and inorganic matrix studies [28, 29]. The synthesis protocol used for these experimental works closely followed the monodisperse synthesis in late 2011 but instead of oleylamine, octadecylamine (ODA) was used.…”
Section: Colloidal Synthesis and Characterization Of Thermal Infraredmentioning
confidence: 99%